2018
DOI: 10.1080/01443615.2018.1433646
|View full text |Cite
|
Sign up to set email alerts
|

Use of ARFI elastography in the prediction of placental invasion anomaly via a new Virtual Touch Quantification Technique

Abstract: We aimed to evaluate the efficiency of placental elasticity in predicting a placental invasion anomaly with the Virtual Touch Quantification (VTQ) technique. Pregnant women in the third trimester with suspected placental invasion anomaly were enrolled into the research (n = 58). The placenta was evaluated and divided into three equal parts as foetal edge (inner 1/3 of placenta), maternal edge (outer 1/3 of placenta) and the central part (central 1/3 of placenta). Shear wave velocity (SWV) measurements were use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 20 publications
2
6
0
Order By: Relevance
“…Accordingly, our study determined that the majority of patients suspected to have API based on elastography values (46/54, 85.2%) were intraoperatively found to have API, and these findings were confirmed histopathologically. The high ARFI values our study determined in patients with API resemble those obtained by Cim and colleagues . Again, similar to our study, a study conducted by Davutoglu et al .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Accordingly, our study determined that the majority of patients suspected to have API based on elastography values (46/54, 85.2%) were intraoperatively found to have API, and these findings were confirmed histopathologically. The high ARFI values our study determined in patients with API resemble those obtained by Cim and colleagues . Again, similar to our study, a study conducted by Davutoglu et al .…”
Section: Discussionsupporting
confidence: 92%
“…Particularly, post‐caesarean section (CS) abnormal uterine scars are thought to serve as a basis for defective decidualization and deep trophoblast invasion . Previous CS and placenta previa in patient history constitute major risk factors for the development of abnormal placental invasion (API) . This condition may lead to massive obstetric hemorrhage, multiple blood transfusions, multiorgan failure, a need for hysterectomy and even mortality .…”
Section: Introductionmentioning
confidence: 99%
“…In our study, the values obtained from the central placenta were higher than the periphery values, indicating the central region was harder, but this may be associated with the fact that the central region was thicker. A recent research study predicting the importance of SWE in placental invasion has revealed that elasticity scores are different among the fetal side, maternal side and central portion of placenta, and the elasticity score is higher in invasive placentas (26). In our measurements performed within the central region itself, consistent with previous studies, the higher velocity of the maternal side may be attributed to the neighborhood surrounding the myometrium, which is harder than the placenta The moderate and high-reliability values of SWE, with inter and intra-observer velocity measurements, are indicative of the fact that it is not a user-dependent test (14).…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, due to increases in the caesarean section rate and uterine cavity operation rate, the incidence of PAS has increased, and the incidence of related postpartum haemorrhage has also increased [6]. Uncontrollable postpartum haemorrhage can occur when PAS is present in combination with placenta previa [7][8][9]. Caesarean section is the main treatment method for PAS, and haemorrhage control during the operation is key for successful treatment.…”
Section: Introductionmentioning
confidence: 99%